The New Offshore Frontiers of EU Energy Security in the Mediterranean: The Politics of Hydrocarbon Development in the Adriatic and Ionian Seas. Issue 3 (3rd July 2017) - Prontera, Andrea
Abstract: Many EU Mediterranean countries are developing national plans for offshore hydrocarbon exploration and production. The transformation of the Mediterranean Sea into a new frontier for EU energy security has raised important concerns about the protection of the fragile marine ecosystem of this semi-enclosed sea. Additional issues have emerged where states' boundaries at sea are not yet defined. This article analyses the emerging international and transnational politics of hydrocarbon development in the Adriatic and Ionian Seas by highlighting the main drivers and effects of the recent relaunch of offshore activities in this region.